A Novel Herbal Composition LI12542F6 Improves Muscle Endurance and Strength in Resistance Trained Males (P23-003-19). (13th June 2019) - Davis, Barbara; Murphy, Jennifer; Gora, Olos
Abstract: Objectives: This study was designed to evaluate the efficacy of an herbal blend composed of Sphaeranthus indicus and Mangifera indica extracts to improve muscle health. Methods: In a randomized, double-blind, placebo-controlled study, 40 male participants of 18–40 yrs age, were assigned to receive 650 mg of LI12542F6 (A) or Placebo (P) for 56 days. The primary endpoint was change from baseline in muscle strength, assessed by 1-RM Bench and Leg presses. Secondary endpoints included muscle endurance, time to exhaustion, muscle size, body composition and free testosterone. Safety was also assessed. Results: Significant ( P < 0.0001) increases in change from baseline for strength (bench and leg presses and grip strength) were observed in the A vs. P group beginning at 14 d and continuing throughout the study. Muscle endurance and time to exhaustion were similarly increased by 14 d and continued for the remainder of the study. By day 56, the mid upper arm circumference was statistically increased in A vs. P ( P < 0.05) in left and right arms. Conclusions: Significant improvements in muscle endurance and strength were observed in resistance trained healthy men consuming LI12542F6 daily for 56 days. Further research will elucidate efficacy in other populations. Funding Sources: Laila Nutraceuticals.